Utilization of Palm Leaf as a Mat (Taker Rakara) in Lembung Barat Village, Lenteng District, Sumenep District - Anggraeni, Mita Martina; Ainiyah, Fina; Millah, Najmatul (META: Journal of Science and Technological Education, 2023)
Indonesia has a diverse biodiversity based on the Wallace line, the Weber line, and the Lydekker line. With this variety, Indonesia is a country with an abundance of natural resources that humans may use. One of its applications is the use of palm leaves in handicrafts. This research is a qualitative study that use a descriptive technique. This is field research, which entails travelling directly to the research location. The research was conducted on March 22-23, 2023, at West Lembung Village, Lenteng District, Sumenep Regency. Data is gathered by observation and documentation. According to study, residents in Lembung Barat Village, Lenteng District, Sumenep Regency frequently utilize palm leaves as the major raw material for manufacturing handicrafts in the shape of mats (Taker Rakara) using basic ways. When the tobacco harvest season approaches, this easy procedure produces a product in the shape of a mat that may be used as a tobacco wrapper.